2020
DOI: 10.3349/ymj.2020.61.10.844
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Experience with Pembrolizumab Treatment in Patients with Heavily Treated Recurrent Gynecologic Malignancies

Abstract: Purpose: We evaluated the efficacy and safety of pembrolizumab in patients with recurrent gynecologic cancers in real-world practice. Materials and Methods: We conducted a retrospective, single-institution study of patients with recurrent gynecologic malignancies treated with pembrolizumab. The primary endpoints were the objective response rate (ORR) and safety. Results: Thirty-one patients treated with pembrolizumab were included. The primary disease sites were the uterine cervix (n=18), ovaries (n=8), and ut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Overall, 18 reviews (21-38) and 8 case reports (39)(40)(41)(42)(43)(44)(45)(46) were identified, while 40 studies were deemed irrelevant. After removal of ineligible studies, 6 studies were recruited (47)(48)(49)(50)(51)(52). After evaluating the references of the eligible studies, three additional articles were identified (53)(54)(55).…”
Section: Data On Efficacy and Safetymentioning
confidence: 99%
See 4 more Smart Citations
“…Overall, 18 reviews (21-38) and 8 case reports (39)(40)(41)(42)(43)(44)(45)(46) were identified, while 40 studies were deemed irrelevant. After removal of ineligible studies, 6 studies were recruited (47)(48)(49)(50)(51)(52). After evaluating the references of the eligible studies, three additional articles were identified (53)(54)(55).…”
Section: Data On Efficacy and Safetymentioning
confidence: 99%
“…After evaluating the references of the eligible studies, three additional articles were identified (53)(54)(55). Overall, 9 studies incorporating data from 712 EC patients were eligible for this systematic review (47)(48)(49)(50)(51)(52)(53)(54)(55). The aforementioned process of the selection of studies is illustrated in Fig.…”
Section: Data On Efficacy and Safetymentioning
confidence: 99%
See 3 more Smart Citations